Conditional vs. Voluntary Contribution Mechanism – An Experimental Study - Andreas Reischmann (University of Heidelberg, Department of Economics, 2015)
The Conditional Contribution Mechanism for public good provision gives all agents the possibility to condition their contribution on the total level of contribution provided by all agents. In this experimental study the mechanism's performance is compared to the performance of the Voluntary Contribution Mechanism. In an environment with binary contribution and linear valuations subjects play the mechanisms in a repeated setting. The mechanisms are compared in one case of complete information and homogeneous valuations and in a second case with heterogeneous valuations and incomplete information. In both cases a significantly higher contribution rate can be observed when the Conditional Contribution Mechanism is used.
urn:nbn:de:bsz:16-heidok-184846
Keywords: 330; Experimental Economics; Public Goods; Mechanism Design; Better Response Dynamics